2006
DOI: 10.1093/cercor/bhj122
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Rule-Based and Information-Integration Visual Category Learning

Abstract: An emerging theory of the neurobiology of category learning postulates that there are separate neural systems supporting the learning of categories based on verbalizeable rules (RB) or through implicit information integration (II). The medial temporal lobe (MTL) is thought to play a crucial role in successful RB categorization, whereas the posterior regions of the caudate are hypothesized to support II categorization. Functional neuroimaging was used to assess activity in these systems during category-learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
227
6
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(251 citation statements)
references
References 45 publications
17
227
6
1
Order By: Relevance
“…Indeed, the current study extends prior fMRI work implicating HPC processes in classification learning (22,(51)(52)(53) to demonstrate the influence of goal-relevant selective attention in HPC-based conceptual representations. These results add support for the theoretical proposal from the episodic memory literature that the HPC adaptively builds knowledge representations across episodes (11,12).…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, the current study extends prior fMRI work implicating HPC processes in classification learning (22,(51)(52)(53) to demonstrate the influence of goal-relevant selective attention in HPC-based conceptual representations. These results add support for the theoretical proposal from the episodic memory literature that the HPC adaptively builds knowledge representations across episodes (11,12).…”
Section: Discussionsupporting
confidence: 73%
“…For example, it is clear that aspects of category learning are mediated by a hippocampal learning system (Foerde, Knowlton, & Poldrack, 2006;Love & Gureckis, 2007), and we have shown that this system may be involved in certain aspects of rule learning (Nomura et al, 2007). However, the present experiment was designed to differentially tap the rule and procedural systems.…”
Section: Discussionmentioning
confidence: 92%
“…The rule and procedural systems rely on distinct neural substrates. The rule system is implemented by a circuit involving dorsolateral prefrontal cortex, anterior cingulate and the head of the caudate nucleus (Ashby & Maddox, 2005;Filoteo et al, 2005;Love & Gureckis, 2007;Seger & Cincotta, 2005, whereas the procedural system is implemented by a circuit involving inferotemporal cortex and the posterior caudate nucleus (Ashby et al, 1998;Nomura et al, 2007;Seger & Cincotta, 2005;Wilson, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…First, a recent II neuroimaging study failed to report taskrelated activation in the putamen (Nomura et al, 2007). Instead, significant striatal activation was limited to the caudate nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of studies have reported that patients with basal ganglia dysfunction are impaired in II tasks (Filoteo, Maddox, & Davis, 2001;Filoteo, Maddox, Salmon, & Song, 2005) and neuroimaging studies of II learning have reported significant learning-related striatal activation (Cincotta & Seger, 2007;DeGutis & D'Esposito, 2007;Nomura et al, 2007;Seger & Cincotta, 2002). In addition, a large literature implicates the striatum in visual discrimination learning and category learning in nonhuman animals (for a review, see Ashby & Ennis, 2006).…”
Section: Introductionmentioning
confidence: 99%